The complete mitochondrial genome of a Chinese endemic stonefly species, Sinacroneuria dabieshana (Plecoptera: Perlidae) - Jinjun Cao; Weihai Li; Ying Wang (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitochondrial genome of Sinacroneuria dabieshana Li & Murányi, the first representative of the genus Sinacroneuria, was sequenced and annotated. This mitogenome was 15,752 bp long and encoded 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes and a control region. The S. dabieshana mitogenome with an A + T content of 67.3% presented a positive AT-skew (0.058) and a negative GC-skew (−0.303). Ten PCGs started with a typical ATN codon, except ATP8, COI and ND1 initiated with GTG, CCG and TTG, respectively. Eleven PCGs use the typical stop codon TAA/TAG, except COII and ND5 gene terminated with a single T. The Bayesian (BI) and maximum-likelihood (ML) trees both showed that S. dabieshana and Acroneuria hainana are the sister group. Phylogenetic relationships among six genera within Perlidae were recovered as (Caroperla + ((Acroneuria + Sinacroneuria) + (Dinocras + (Togoperla + Kamimuria)))).